ANALYZING E-COMMERCE OF SMALL AND MEDIUM-SIZED ENTERPRISES IN THE EUROPEAN UNION: DEPENDENCIES AND TRENDS IN THE CONTEXT OF DIGITALIZATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The presented study analyses the implementation of e-commerce by small and medium-sized enterprises in the countries of the European Union. The main objective of the study is, based on analysing the sales of small and medium-sized enterprises in e-commerce by enterprise size and the relative share of turnover obtained from e-commerce, during the period 2013-2023, to identify the emerging dependencies, as well as to establish development trends. The importance of the digitalization of the business of small and medium-sized enterprises through e-commerce is emphasized. Development trends are established and the indicator for the average annual growth rate is determined. The adopted methodological framework for conducting the study includes the application of the IBM SPSS Statistics software product, the Excel program, as well as the use of the linear regression and correlation method. The respondents of the study are a set of small and medium-sized enterprises from the 27-member states of the European Union. The results of the analysis show that the relative share of SMEs in the countries studied that engage in e-commerce and the turnover generated by e-sales vary significantly over the period under analysis. Differences are identified across European countries. The business opportunities of SMEs to implement e-commerce in digital environments are interpreted. Such studies help to identify upcoming changes in the business models of European SMEs.